Feeding, management and health care practices of dairy cattle farms in Nepal - Dhungana, Jyoti; Gauchan, Devendra; Panta, Hari Krishna; Timsina, Krishna Prasad; Paudel, Loknath (Journal of Agriculture and Natural Resources, 2025)
Dairy farming is an important source of income for farmers; however, farm management practices are often overlooked. Therefore, this study aims to assess the feeding, management, and healthcare practices of dairy cattle farms in Nepal. A total of 407 households were surveyed in the districts of Ilam (86), Morang (114), Kavre (91), and Chitwan (116). The data was collected from February to October 2024. Descriptive statistics were used to compare the mean and frequency. Farms were compared using one-way ANOVA, with a post hoc test to examine variation among farm sizes. The findings revealed that 93.1% of farmers fed rice straw, while 80.8% fed Kundo or Khole as the primary feed. Feed blocks, UMMB, and urea molasses were used by 19.4%, 20.1%, and 6.4% of the farms, respectively. Similarly, on average, 45% of cattle housing was found in good condition, while 45.2% had a mud-floor mix with concrete. The adoption rate for GHPs such as disinfectant (4.9%), protective workers (16.5%), farm entry log (4.9%), grooming tools (24.1%), and record keeping (23.3%) was found to be low. The technology adoption remains at seven or fewer for 71.5% cattle farms. Mastitis (44%) was the most reported disease, followed by FMD (25%), infertility (14%), Charchare (5%), and other diseases, including lumpy skin (12%). 35.3% farms followed regular health care services, while 64.7% practiced it irregularly. In addition, the economic analysis revealed that 71% and 29% of the cost was covered by feed and non-feed inputs, respectively, while the medium-sized farm was identified as the most profitable. It is suggested to provide training and extension services on good husbandry practices, along with increasing subsidies for improved farming techniques to lower costs. Further, preventive measures for disease control, including surveillance and quarantine, are essential.